Growth and electronic structure of graphene on semiconducting Ge(110). (October 2017) - Tesch, Julia; Voloshina, Elena; Fonin, Mikhail; Dedkov, Yuriy
Abstract: The direct growth of graphene on semiconducting or insulating substrates might help to overcome main drawbacks of metal-based synthesis, like metal-atom contaminations of graphene, transfer issues, etc. Here we present the growth of graphene on n -doped semiconducting Ge(110) by using an atomic carbon source and the study of the structural and electronic properties of the obtained interface. We found that graphene interacts weakly with the underlying Ge(110) substrate that keeps graphene's electronic structure almost intact promoting this interface for future graphene-semiconductor applications. The effect of dopants in Ge on the electronic properties of graphene is also discussed. Graphical abstract: